What Should Be the EU's Approach to Global Trade? - Annette Bongardt; Francisco Torres (Intereconomics, 2018)
For a global player like the EU, it must adequately respond to US unilateral actions and not give in to threats in order to preserve its credibility. However, it is not in its interest to let trade conflicts escalate and be drawn into trade wars. It is worth noting that through the bilateral rules established in the context of a comprehensive trade agreement, the EU not only influences global norms and standards but that those in turn feed back into the EU's economic order in a way that traditional trade agreements have not. They can therefore either reinforce the European model or weaken it.
Keywords: 330; European governance; Trade disputes; Trade policy; Trade restrictions; WTO